2014
DOI: 10.1002/micr.22271
|View full text |Cite
|
Sign up to set email alerts
|

Free perforator flap transfer for reconstruction of skull base defects after resection of advanced recurrent tumor

Abstract: The use of perforator flaps may be a viable option for reconstruction of skull base defects after the resection of advanced recurrent tumor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
12
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 16 publications
0
12
0
Order By: Relevance
“…Although this may be the preferred technique whenever a longer pedicle is required, concerns have been raised about the vascularity of such flaps. The free thoracodorsal (TD) artery perforator flap has been used for the various reconstruction from head and neck region to lower extremities . The aim of this study was to assess the safety and reliability of TD artery perforator flaps harvested with centrally or eccentrically located perforators.…”
mentioning
confidence: 99%
“…Although this may be the preferred technique whenever a longer pedicle is required, concerns have been raised about the vascularity of such flaps. The free thoracodorsal (TD) artery perforator flap has been used for the various reconstruction from head and neck region to lower extremities . The aim of this study was to assess the safety and reliability of TD artery perforator flaps harvested with centrally or eccentrically located perforators.…”
mentioning
confidence: 99%
“…The thoracodorsal artery perforator flap has been reliably used for various reconstruction operations ranging from head and neck reconstruction to hand resurfacing . The thickness of this flap can be safely reduced to about 5 mm.…”
Section: Discussionmentioning
confidence: 99%
“…Second, the conversion to a trapezius musculocutaneous or muscle flap could be a safer solution rather than continuing to search for an additional perforator. Of course, before proceeding with a pedicled DSAP flap, a free flap should be also considered during surgery planning because it has proven to be an effective option in reconstruction of the posterior scalp and neck …”
Section: Discussionmentioning
confidence: 99%
“…Of course, before proceeding with a pedicled DSAP flap, a free flap should be also considered during surgery planning because it has proven to be an effective option in reconstruction of the posterior scalp and neck. 11,12 The trapezius musculocutaneous flap has been regarded as an easy and useful modality suited to head and neck reconstruction with minor donor site morbidity. However, Angrigiani et al 2 reported 20% mild restriction of shoulder movement to be caused by sacrificing the trapezius muscle, despite including a 25-cm 2 muscle cuff around the perforator, and Haas et al 4 emphasized the utmost importance of preserving as much function as possible when considering role of the trapezius muscle in shoulder function: stabilizing and moving the scapula and elevating the shoulder.…”
Section: Discussionmentioning
confidence: 99%